Deeply Cycled Sodium Metal Anodes at Low Temperature and in Lean Electrolyte Conditions - Hu, Xiaofei; Matios, Edward; Zhang, Yiwen; Wang, Chuanlong; Luo, Jianmin; Li, Weiyang (Angewandte Chemie International Edition, 2021)
Enabling high‐performing alkali metal anodes at low temperature and in lean electrolyte conditions is critical for the advancement of next‐generation batteries with high energy density and improved safety. We present an ether–ionic liquid composite electrolyte to tackle the problem of dendrite growth of metallic sodium anode at low temperatures ranging from 0 to −40 °C. This composite electrolyte enables a stable sodium metal anode to be deeply cycled at 2 mA cm−2 with an ultrahigh reversible capacity of 50 mAh cm−2 for 500 hours at −20 °C in lean electrolyte (1.0 μL mAh−1) conditions. Using the composite electrolyte, full cells with Na3V2(PO4)3 as cathode and sodium metal as anode present a high capacity retention of 90.7 % after 1,000 cycles at 2C at −20 °C. The sodium–carbon dioxide batteries also exhibit a reversible capacity of 1,000 mAh g−1 over 50 cycles across a range of temperatures from −20 to 25 °C. An ether–ionic liquid composite electrolyte with fast ion transport, superior desolvation capability, and high electrochemical stability is exploited to suppress sodium dendrite growth at low temperatures ranging from 0 to −40 °C. This composite electrolyte enables a stable sodium metal anode to be deeply cycled with an ultrahigh reversible capacity of 50 mAh cm−2 for 500 hours at −20 °C in lean electrolyte (1.0 μL mAh−1) conditions.